Isu Munakahat di Kalangan Orang Kurang Upaya (OKU) Pendengaran - Azman Ab Rahman; NorFatihah Amlin Ab Ghan; Mohamad Anwar Zakaria; Mursyid Junaidi Mohd Faisal Yeap (USIM Press, 2024)
Vol. 4 No. 1 (2020)